Formação pedagógica e ação docente: processo de colocação dos professores na Escola do Primeiro Cíclo do Ensino Secundário em Cabinda, Angola - Juliana Ndulo Cumba Josefa (2014)
The research Pedagogic Formation and Instructional Action: the Teachers Placing Process at the Primary Cycle of High School level in Cabinda, Angola was developed because of the necessity to understand and to explain the problematic involved in the relevance of pedagogic formation in teaching actions, taking into account the heterogeneous profile verified in the teaching staff of Angolas schools in general, and focusing on the Primary Cycle of the High School level from Luvassa, Cabinda, which was the sample space chosen to conduct this research. The heterogeneity consists in the cohabitation of pedagogically instructed teachers with non pedagogically instructed ones. However, even those who are pedagogically intructed had to work with disciplines unrelated to their specialties and fields. Alongside the theoretical support given by Peterson (2003), Tardif (2012), Perrenoud (2001) and others about the teachears development programmes and based in a qualitative approach, we were able to analyse the lessons in two biology classes. Only one of them had an initial pedagogic formation. We could also observe the strategies used by each of them in the classroom during the school term. To complement the data collected during the observations, we applied two questionnaires using 67 teachers as a sample space and also made two interviews, one of them with the two aforementioned teachers, and the other with four teachers. Our aim was to explore what their professional practices and literacy represented to them. Given the obtained results, we were able to question, in a certain scale, the supremacy of pedagogic formation in the teaching process, but without discarding its importance.